Improved Combustion of Asphaltite Coals in a Rotating Head Combustor with Various Air Supply Arrangements - Oner, Cengiz; Altun, Sehmus (Amer Chemical Soc, 2014)
When burned in conventional stokers, coals with high swelling properties such as asphaltites make coke blocks (coking). The plastic layer formed on them prevents air from diffusing into coal; hence, the air provided for swollen coal to burn becomes insufficient. This problem can partially be resolved by shaking the flame bed automatically or by mixing the burning coals manually in order to provide continuous air for the surface of the unburned coal. Therefore, in this study, a coal combustion system with the rotating head was manufactured for burning effectively Turkish coking coals characterized by high sulfur and ash content in agitation conditions with air supply arrangements. This type of coals known as asphaltite, abundantly found in southeastern Anatolia coal basin in Turkey, were burned in the rotating head combustor in order to investigate the effect of operating parameters, such as excess air ratio, coal particle size and feeding speed, air delivery type, addition of flange, bed slope, and rotation speed on the combustion efficiency and temperature distribution on the head. Experimental results showed that both the rotating of combustion chamber and additional air supply, which was blown out with pressure from the air delivery holes, reduced the negative impact of ash on the combustion efficiency, mainly due to the coal getting in touch with air better. It was possible to increase the peak combustion efficiency over 80% by both improving the air supply and agitation of coalbed preventing coking during combustion. As a result, this system could be highly recommended to burn the coals with high swelling properties like asphaltite at a high efficiency.
Keywords: Pyrolysis